Autoimmune colitis and neutropenia in adjuvant anti-PD-1 therapy for malignant melanoma: efficacy of Vedolizumab, a case report. (January 2022) - d'Apolito, Maria; Spagnuolo, Rocco; Siciliano, Maria Anna; Barbieri, Vito; Cosco, Cristina; Fiorillo, Lucia; Cuomo, Onofrio; Zuccalà, Valeria; Correale, Pierpaolo; Pensabene, Licia; Rossi, Marco; Doldo, Patrizia; et al.
Immune checkpoint inhibitors (ICIs) represent an important advance in the adjuvant treatment of patients with high-risk melanoma. Although the safety profile of anti-programmed cell death protein-1 (PD-1) is fairly acceptable, different immune-related adverse events (irAEs) are described. Herein we report for the first time a notably multidisciplinary combined approach on a malignant melanoma (MM) patient treated with anti-PD-1 antibody in adjuvant setting. In this novel approach, corticosteroid-refractory immune-mediated colitis (IMC) was effectively treated with Vedolizumab, a selective blockade of the α4β7 integrin and corticosteroids were successfully administered for autoimmune neutropenia. Notably, our patient also express HLA-B*35, a potential biomarker for predicting a genetic basis of autoimmune susceptibility. Our experience offers a possible future perspective about the use of Vedolizumab together with immunotherapy in a strategic early approach for high-risk patients genotyped for HLA.